Relevance of menopausal status in mental health differences be-tween women and men - Matud, Maria-Pilar; Correa, Maria-Concepcion; Bethencourt, Juan-Manuel; Del Pino, Maria-Jose (Anales de Psicología / Annals of Psychology, 2014)
The objective of this study is to examine differences between men and women in self-esteem and depressive, somatic and anxiety symptoms when studying the relevance of menopausal status and age in such differences. Research design was a cross-sectional survey of a general population sample of 1341 (n = 726 women and n = 615 men) adults of different ages and, in the case of women, with different menopausal status. Participants responded to Goldberg General Health Questionnaire and Rector and Roger Self-esteem questionnaire. Results showed that women had more anxiety and somatic symptoms than men. Gender differences in depressive symptoms and self-esteem were not found in younger participants, although women over 40 showed more depressive symptoms and lower self-esteem than men of similar ages. Intra-gender analysis indicated that younger men had more depressive symptoms and less self-esteem than those over 40, whereas these differences were not observed in the women sample. Differences among women were only observed in relation with their diverse menopausal status in somatic symptoms, these latter being greater in perimenopausal than in premenopausal women. These results make clear that menopause has little relevance in gender differences in mental health.